The Effect of Healthy Lifestyle and Accessibility of Health Facilities on Quality of Life and Life Expectancy of Communities in Jakarta - Ni Desak Made Santi Diwyarthi; I Wayan Jata; Nyoman Gede Mas Wiartha; I Wayan Adi Pratama (West Science Interdisciplinary Studies, 2023)
This research investigates the intricate relationships between healthy lifestyle practices, the accessibility of health facilities, and their impact on the quality of life and life expectancy in Jakarta. Employing a quantitative approach with a sample of 300 participants, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the data. The measurement model confirms the reliability and validity of latent constructs, while the structural model reveals significant positive associations. Improved accessibility of health facilities is strongly linked to higher life expectancy and better quality of life. Additionally, healthier lifestyle practices positively influence both life expectancy and quality of life. The statistical tests further support these relationships, emphasizing the critical role of healthcare infrastructure and individual choices in shaping public health outcomes. The findings provide actionable insights for public health interventions and policy development to enhance the overall well-being of Jakarta's residents.